2013
DOI: 10.1002/art.37784
|View full text |Cite
|
Sign up to set email alerts
|

Am80, a retinoic acid receptor agonist, ameliorates murine vasculitis through the suppression of neutrophil migration and activation

Abstract: Objective. Vasculitis is characterized by leukocyte infiltration in the vessel walls, with destructive damage to mural structures. Retinoids are compounds that bind to retinoic acid receptors and exert biologic activities similar to those of vitamin A, including modulatory effects on cell proliferation and differentiation. This study was undertaken to examine the therapeutic effects of a synthetic retinoid, Am80, in a murine model of vasculitis induced by Candida albicans water-soluble fraction (CAWS). Vasculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…The results of recent studies have shown that Am80 is capable of suppressing experimental autoimmune diseases and chronic graft-versus-host disease. [19][20][21][22] We have also demonstrated that treatment by Am80 ameliorates experimental autoimmune uveoretinitis during the entire phase of the disease. 23 Am80 is a RAR α/β-selective retinoid that dose not bind and activate RAR-γ and RXRs, hence can reduce the unfa-vourable adverse effects.…”
Section: Discussionmentioning
confidence: 75%
“…The results of recent studies have shown that Am80 is capable of suppressing experimental autoimmune diseases and chronic graft-versus-host disease. [19][20][21][22] We have also demonstrated that treatment by Am80 ameliorates experimental autoimmune uveoretinitis during the entire phase of the disease. 23 Am80 is a RAR α/β-selective retinoid that dose not bind and activate RAR-γ and RXRs, hence can reduce the unfa-vourable adverse effects.…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, neutrophils play an important role in CAWS-vasculitis and exhibit the characteristics of neutrophils such as (i) prolonged survival in inflammatory tissue, (ii) the production of a variety of inflammatory and tissue mediators in blood vessels, such as reactive oxygen species, arachidonate metabolites, proteases and glycosidases, are strongly related to the degradation and remodeling of blood vessels 36,37 . Furthermore, we found that CCR2, a receptor for MCP-1, deficient mice were resistant to CAWS-vasculitis 10 .…”
Section: Discussionmentioning
confidence: 99%
“…KD-like vasculitis can be induced in rabbit, swine, and mouse models by various methods (80)(81)(82)(83). The known genetic background and ease of genetic manipulation have made mouse models the preferred model to investigate molecular pathogenesis of KD and to discover its therapeutic targets (84)(85)(86)(87)(88).…”
Section: Insight From Experimental Studies With Animal Model For Kdmentioning
confidence: 99%